Implementation of Fused Filament Fabrication in Dentistry - Jörg Lüchtenborg; Felix Burkhardt; Julian Nold; Severin Rothlauf; Christian Wesemann; Stefano Pieralli; Gregor Wemken; Siegbert Witkowski; Benedikt C. Spies (Applied Sciences, 2021)
Additive manufacturing is becoming an increasingly important technique for the production of dental restorations and assistive devices. The most commonly used systems are based on vat polymerization, e.g., stereolithography (SLA) and digital light processing (DLP). In contrast, fused filament fabrication (FFF), also known under the brand name fused deposition modeling (FDM), is rarely applied in the dental field. This might be due to the reduced accuracy and resolution of FFF compared to vat polymerization. However, the use of FFF in the dental sector seems very promising for in-house production since it presents a cost-effective and straight forward method. The manufacturing of nearly ready-to-use parts with only minimal post-processing can be considered highly advantageous. Therefore, the objective was to implement FFF in a digital dental workflow. The present report demonstrates the production of surgical guides for implant insertion by FFF. Furthermore, a novel approach using a temperature-sensitive filament for bite registration plates holds great promise for a simplified workflow. In combination with a medical-grade filament, a multi-material impression tray was printed for optimized impression taking of edentulous patients. Compared to the conventional way, the printed thermoplastic material is pleasant to model and can allow clean and fast work on the patient.